Unveiling the gender gap in research: a bibliometric analysis of the 100 most-cited articles on food-borne pathogen outbreaks from 1990 to 2020 - Naseer, Bisal; Insaf Ahmed, Rawal Alias; Ali, Mohsan; Talha, Muhammad; Azizullah, Saad; Anwar, Amar (German Medical Science GMS Publishing House, 2024)
Introduction: Despite a recent increase in the representation of female authors in scientific literature, a significant gap persists concerning the inclusion of women in research. This necessitates the analysis of published literature from a gender perspective. This study aimed to provide gender distribution in authorship in the 100 most-cited articles on food-borne pathogen outbreaks from 1990 to 2020.Methods: Bibliometric analysis was conducted using the Scopus database. Two reviewers were selected to search the database. We included the 100 most-cited articles on foodborne outbreak investigations. The analysis was conducted using Statistical Package for Social Sciences (SPSS) version 26 and Microsoft Excel version 2016. The citation data, including total citations, citations per year, and representation of women as first and senior authors, was analyzed in terms of frequencies, mean, median, and interquartile range. The correlation between journal impact factor and the representation of women in high-impact factor journals was determined. A p-value of <0.05 was considered significant.Results: Most of the top-cited articles were published between 2001 and 2010 (n=47). The top 3 most-cited articles were from the USA. Of the total 100 articles, women were the first and last authors in 46% and 28% of the articles, respectively, reflecting a significant gender gap. However, the proportion of females as principal investigators gradually increased from 25% (n=10/30) to 52% (n=24/47) during the period 2001-2010 and to 92% (n=12/13) during 2011-2020. The USA had the highest number of included articles (n=48), and women were principal authors in 56% (n=27) of them. The lowest representation of women was observed in Austria, Denmark, Japan, Netherlands, New Zealand, Nigeria, Portugal, and the United Kingdom.Conclusion: Women are under-represented in published literature on food-borne pathogen outbreaks. Although the representation of women as principal authors has recently increased, disparities still exist at the senior-author level, calling for women's advancement in academic science.